"Story Time!": Coping with Low-Motivated Students using Big Book - Ignatius Javier C. Tuerah (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: Reading the picture book provides students with numerous positive effects, especially young students, such as attracting students' interest, boosting creativity, providing a pleasant, relaxed vibe, and creating fun and meaningful learning. This research seeks to investigate whether the reading comprehension of low-motivated students who are taught with the big book or with the daily storybook varies significantly. Methodology: This study used quasi-experiments, and each group received treatment eight times. The participants were 44 students recruited to become the sample of this study, consisting of experiment and control groups. Findings: This study revealed that students with low motivation who taught with Big Book as a platform are better than students with low motivation taught on traditional media. Several factors have made a big book an instrument that has a more significant impact on students' perception of reading than conventional media. Secondly, students engaged more in-class reading than in conventional media. Thirdly, the book sparked the interest of students and inspired them to learn more. Fourthly, the Big Book helped students create the meaning of the text and appreciate the text more thoroughly. Conclusion: English oral books such as Big-Book are more effective than traditional content in the second year. This study and published data support this conclusion that using large books as a tool for second years' reading understanding affects students' understanding of lectures significantly. The statistical study has found that the total student readership in the test group is higher than the average student score in the control group. Keywords: reading comprehension; low motivation; pupils; picture book.